Transcriptome Analysis Reveals Distinct Responses to Physiologic versus Toxic Manganese Exposure in Human Neuroblastoma Cells - Fernandes, Jolyn; Chandler, Joshua D.; Lili, Loukia N.; Uppal, Karan; Hu, Xin; Hao, Li; Go, Young-Mi; Jones, Dean P. (Frontiers in Genetics, 2019)
Manganese (Mn) is an essential trace element, which also causes neurotoxicity in exposed occupational workers. Mn causes mitochondrial toxicity; however little is known about transcriptional responses discriminated by physiological and toxicological levels of Mn. Identification of such mechanisms could provide means to evaluate risk of Mn toxicity and also potential avenues to protect against adverse effects. To study the Mn dose-response effects on transcription, analyzed by RNA-Seq, we used human SH-SY5Y neuroblastoma cells exposed for 5 h to Mn (0 to 100 μM), a time point where no immediate cell death occurred at any of the doses. Results showed widespread effects on abundance of protein coding genes for metabolism of reactive oxygen species, energy sensing, glycolysis, protein homeostasis including the unfolded protein response and transcriptional regulation. Exposure to a concentration (10 μM Mn for 5 h) that did not result in cell death after 24 h increased abundance of differentially expressed genes (DEGs) in the protein secretion pathway that function in protein trafficking and cellular homeostasis. These include BET1 (Golgi vesicular membrane trafficking protein), ADAM10 (ADAM metallopeptidase domain 10) and ARFGAP3 (ADP-ribosylation factor GTPase activating protein 3). In contrast, 5 h exposure to 100 μM Mn, a concentration that caused cell death after 24 h, increased abundance of DEGs for components of the mitochondrial oxidative phosphorylation pathway. Integrated pathway analysis results showed that protein secretion gene set were associated with amino acid metabolites in response to 10 μM Mn, while oxidative phosphorylation gene set were associated with energy, lipid and neurotransmitter metabolites at 100 μM Mn. These results show that differential effects of Mn occur at a concentration, which does not cause subsequent cell death compared to a concentration that causes subsequent cell death. If these responses translate to effects on the secretory pathway and mitochondrial functions in vivo, differential activities of these systems could provide a sensitive basis to discriminate sub-toxic and toxic environmental and occupational Mn exposures.